Passado e futuro de Feira de Santana (BA): modelagem da dinâmica espacial do uso do solo entre 2000 e 2022 - Santos, Bethsaide Souza (2019)
Identifying urban growth trends is one of the most significant studies for city planning, and Feira de Santana, a medium-sized city, has shown intense growth booms in the last 30 years. Therefore, this work has the main objective of simulating the dynamics of urban land use. Land use change modeling experiments have been performed for the city along multitemporal series of 18 years. The land use transitions were estimated using probabilistic methods. The land use change probabilities thereof obtained drove a cellular automata model. The results of the simulations were spatially validated by means of to a statistical procedures. After completing the simulations for successive cycles of time along the multitemporal series, simulations of future scenarios of transition trends were carried out. It was then possible to evaluate the weight of predefined variables for the various land use changes and to ossess expansion vectors for the years 2020 and 2022